Smart Technologies for the Digitisation of Industry: Entrepreneurial Environment - Inshakova, Agnessa O.; Frolova, Evgenia E.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book discusses fusion of technology and body of knowledge through elaboration of theoretical concepts and conceptual frameworks to ensure the economic growth of the Russian Federation by utilizing the huge potential for innovation and entrepreneurship in Russia. The book presents recent research to solve the most challenging problems facing digitalization in the field of entrepreneurship in the country. Some of them need specialized personnel training; the considerable financial resources needed for the maintenance of digital technologies; how to market enterprises and organizations; and financial instruments designed to support industrial development. The proposed results will create the conditions for a systemic approach to tilting towards supporting new ventures through an improved regulatory framework currently virtually absent in the field of entrepreneurship at the national level. The book defines prospects for investment in renewable energy sources, circulation of energy resources, and energy efficiency improvements to gain positive economic effects from the introduction of new technologies. .
Digital Platforms and Cloud Technologies in Post-Capitalist Discourse: a Doctrinal and Legal Perspective -- Utilizing Artificial Intelligence in Legal Practice -- Augmented Reality and Civil Law Regulation of Business Relations -- A Typology of Risks and Threats Associated with the Digital Transformation of Economic and Legal Systems -- Prospects for the Use of Cross-Cutting Digital Technologies in the Framework of Tax and Currency Control over Cross-Border Financial Transactions -- Medical Cluster as a Tool of Innovative Economy: Legal Aspects -- International Cooperation in the Field of Economic and Legal Regulation of End-to-End Technologies -- New Challenges of International Legal Regime and Use of Artificial Intelligence -- Legal Mechanisms for Protecting the Rights of Economic Entities in the Conditions of Development Penetrative Technologies -- Introduction of Digital Methods of Protection of Rights as a Legal Guarantee of Business Activity in the Modern World -- Using Artificial Intelligence in Dispute Resolution -- Smart Contracts in the Digital Economy: Contractual Regulation and Dispute Resolution.
Keywords: Industrial engineering; Production engineering; Technology Sociological aspects; Information technology; Cloud Computing; Artificial intelligence; Industrial and Production Engineering; Emerging Technologies; Information and Communication Technologies (ICT).; Cloud Computing; Artificial Intelligence; Sustainable development -- Russia (Federation); Russia (Federation) -- Economic policy; Russia (Federation) -- Economic conditions